A Viable Passive Optical Network Design for Ultrahigh Definition TV Distribution. (16th May 2013) - Niazi, Shahab Ahmad; Zhang, Xiaoguang; Xi, Lixia; Munir, Abid; Idrees, Muhammad; Khan, Yousaf
Abstract : International Telecommunication Union (ITU) has recently standardized ultrahigh definition television (UHD-TV) with a resolution 16 times more than the current high definition TV. An increase in the efficiency of video source coding or in the capacity of transmission channels will be needed to deliver such programs by passive optical network (PON). In this paper, a high capacity integrated PON infrastructure is proposed to overlay ultrahigh definition television by a complete passive coexistence of 10G-PON (XG-PON) and single carrier directly modulated, duo-binary 40G-PON (XLG-PON) signal. The simulation results show error-free transmission performance and further distribution to 32 optical network units (ONUs) on broadcast basis with negligible power penalty over 20 km of bidirectional standard single mode fiber.